The community preference principle in labour migration policy in the European Union - Robin-Olivier, Sophie (Paris, 2016)
"This paper is part of the joint project between the Directorate General for Migration and Home Affairs of the European Commission and the OECD’s Directorate for Employment, Labour and Social Affairs on "Review of Labour Migration Policy in Europe". This document has been produced with the financial assistance of the European Union. The views expressed herein can in no way be taken to reflect the official opinion of the European Union. Grant: HOME/2013/EIFX/CA/002 / 30-CE-0615920/00-38 (DI130895) A previous version of this paper was presented and discussed at the OECD Working Party on Migration in June 2015.The paper investigates the notion of the "community preference" which in filling job posts gives a priority to EU-nationals over third-country nationals. Analysing the impact of the principle on the European labour migration policy, the report presents a brief history of the notion, and discusses how it is referred to in EU labour migration policy documents. It also examines the challenges that the principle is facing as the EU immigration policy develops, tending to give increasing rights to third-country nationals."